The Effect of soybean Meal substitutions with Fermented water spinach leaves meal (Ipomoea aquatic Forsk) in artificial Diet on the growth of green catfish (Hemibagrus nemurus) Fingerlings - Nababan, Fatisah; Adelina, Adelina; Suharman, Indra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT                This research was conducted in September-November 2018. The aim of this research was determine the effect of substitution soybean meal with fermented water spinach leaves(Ipomoea aquatic Forsk) in diet on feed efficiency and growth of green catfish(Hemibagrus nemurus). This research used Completely Randomized Design (CRD) with one factor 5 treatments and 3replications. The treatment in this research was the use of Fermented water spinach leaves (FWSL) meal  in diet different proportions namely P1(0% FWSL), P2 (5% FWSL), P3 (10% FWSL), P4 (15% FWSL) and P5 (20% FWSL). The results showed that the best treatment was found in P4 which was produced 67% feed digestibility, 3,89% specific growth rate, 37,46% feed efficiency of  catfish.  Keywords: Artifical feed, Hemibagrus nemurus, Fermentation, soybean, water